Pendidikan multikultural : cross-cultural understanding untuk demokrasi dan keadilan - Yaqin, M. Ainul, 1974-; Abdullah, Amin; Muarif; Az, Sugiyarto (Yogyakarta : Pilar Media, 2005)
Multicultural education in a pluralistic society of Indonesia to develop cross-cultural understanding towards democracy .
Includes bibliographical references (p. 297-305) and index.
Keywords: Multicultural education -- Indonesia